Crescimento alométrico e o uso da relação peso e comprimento na avaliação espacial da abundância e condição corporal de peixes juvenis - Santiago, Diogo Fernandes (Universidade Federal de São Carlos, 2022)
Coastal ecosystems such as estuaries and coastal lagoons have a great economic, ecological and social importance. Vegetated habitats such as mangroves and marshes are recognized for acting as nursery areas for juvenile fish, due to the fact that they provide areas of refuge Against predators, greater availability of food and provide an accelerated growth of juvenile fish. However, the intense environmental degradation and the inappropriate use of its resources by humanity threaten the coastal ecosystem services of these environments. The data extracted from the weight and length relationship (LW) have applicability in several ecological studies and for fisheries science. In this sense, the general objective was to explore ecological and biological aspects through the relationship approach (LW). Initially, relationships (LW) were adjusted, and their parameters were estimated. Allometric growth type (positive allometric; negative allometric; isometric) was tested for juvenile fish caught in an estuary in the Neotropics. In addition, the extreme values (higher and lower) of the parameter b of the relationships (LW) were evaluated regarding the body shape of the fish. Finally, the influence of different habitats on the abundance and body condition of juvenile fish of Atherinella brasiliensis was tested. Twenty-two relationships (LW) were adjusted for fish in the juvenile phase, and the predominant type of growth (54.54%) was isometric, showing that most species of juveniles increase their body dimensions in the same proportion. The body shape of the species partly explains the extreme values (higher and lower) of parameter b. Furthermore, the results of the second chapter indicate that saltmarsh habitats seem to increase the nursery value for juvenile A. brasiliensis individuals, probably due to the presence of abundant vegetation and its associated resources
Allometric growth and the use of weight-length relationship in the spatial evaluation of abundance and body condition of juvenile fish
Keywords: Ecossistemas costeiros; Berçário; Peixes juvenis; Relação Peso-Comprimento; Habitats estuarinos; Coastal Ecosystems; Nursery; Juvenile Fish; Weight-Length Relationship; Estuarine Habitats; CIENCIAS BIOLOGICAS::ECOLOGIA